From death to birth: how osteocyte death promotes osteoclast formation - Zhao, Weijie; Qian, Jiale; Li, Ji; Su, Tian; Deng, Xiaozhong; Fu, Yonghua; Liang, Xuelong; Cui, Hongwang (Frontiers in Immunology, 2025)
Bone remodeling is a dynamic and continuous process involving three components: bone formation mediated by osteoblasts, bone resorption mediated by osteoclasts, and bone formation-resorption balancing regulated by osteocytes. Excessive osteocyte death is found in various bone diseases, such as postmenopausal osteoporosis (PMOP), and osteoclasts are found increased and activated at osteocyte death sites. Currently, apart from apoptosis and necrosis as previously established, more forms of cell death are reported, including necroptosis, ferroptosis and pyroptosis. These forms of cell death play important role in the development of inflammatory diseases and bone diseases. Increasing studies have revealed that various forms of osteocyte death promote osteoclast formation via different mechanism, including actively secreting pro-inflammatory and pro-osteoclastogenic cytokines, such as tumor necrosis factor alpha (TNF-α) and receptor activator of nuclear factor-kappa B ligand (RANKL), or passively releasing pro-inflammatory damage associated molecule patterns (DAMPs), such as high mobility group box 1 (HMGB1). This review summarizes the established and potential mechanisms by which various forms of osteocyte death regulate osteoclast formation, aiming to provide better understanding of bone disease development and therapeutic target.